Nucleotide supplementation and the growth of term small for gestational age infants. - Cosgrove, M. (BMJ Group, 1996)
A double blind randomised controlled trial in small for gestational age (SGA) infants, whose intestinal mucosa was shown to be functionally impaired as a result of intrauterine undernutrition, was carried out to investigate the hypothesis that nucleotide supplementation of a milk formula could improve catchup growth. Anthropometric data were collected on 74 infants, 39 randomly allocated to the nucleotide supplemented group (group N) and 35 to a standard formula group (group S). From study entry to 2 months of age, infants in group N had significantly higher mean rates of weight gain (106.3 compared with 94.7 g/kg baseline weight/week) and length gain (21.8 v 19.7 mm/m baseline length/week). Over the whole six months for which the trial formula was provided group N had significantly higher mean rates of gain of weight (80.1 compared with 71.8 g/kg baseline weight/week), length (16.2 compared with 15.0 mm/m baseline length/week), and head circumference (11.8 compared with 10.8 mm/m baseline head circumference/week). Catchup growth in SGA infants is therefore improved by nucleotide supplementation of infant formula.